Pembuatan Sistem Monitoring Shell and Tube Heat Exchanger - Edi Karyadi Edi Karyadi; Rusadi Rusadi; Hadimi Hadimi; Tri Widayanti Tri Widayanti (Vokasi: Jurnal Publikasi Ilmiah, 2025)
A Heat exchanger is a unit that heats a liquid fluid by absorbing heat from another energy source. Heat transfer occurs when a fluid with a higher temperature moves to a fluid with a lower temperature. A shell and tube Heat exchanger has two main components: the shell and the tube, with one fluid flowing inside the tube and the other flowing outside the tube (the shell). Temperature is a physical quantity that needs to be controlled and monitored in a shell and tube heat exchanger, particularly at the input and output sides. To obtain more accurate and real-time measurement results, a shell and tube monitoring system based on an Arduino Uno microcontroller was created. This system consists of a K-type thermocouple, a microcontroller (Arduino UNO), a 20X4 LCD, and a MAX 6675 module